2018
DOI: 10.1139/apnm-2018-0107
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-induced oxidative stress, acetylcholinesterase inhibition, and mediated brain injury attenuated byThymus algeriensis

Abstract: The aim of the current study was to evaluate acetylcholinesterase (AChE) inhibition, antioxidant enzyme activities, and malondialdehyde (MDA) levels induced by hydrophobic fractions of Thymus algeriensis (HFTS) growing in Tunisia. The results showed that hydrogen peroxide (HO), an oxidative stress inducer, acts by decreasing the body mass and brain mass of rats. Moreover, we found higher MDA levels in the group treated with HO (P < 0.05) and a significantly lower activity of catalase, glutathione peroxidase, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…The reduction of NOX-1 by both extracts may contribute to their protective effects against neuropathic pain. Our findings are consistent with those of a study that reported that TA extract has antioxidant potential and neuroprotective effect in a rat model of H2O2induced brain injury 14 . According to previous studies, the sciatic nerve injury was reported to be responsible for the increase in gene expression of iNOS and NO in spinal cord microglial cells by the 5 th day post-surgery.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction of NOX-1 by both extracts may contribute to their protective effects against neuropathic pain. Our findings are consistent with those of a study that reported that TA extract has antioxidant potential and neuroprotective effect in a rat model of H2O2induced brain injury 14 . According to previous studies, the sciatic nerve injury was reported to be responsible for the increase in gene expression of iNOS and NO in spinal cord microglial cells by the 5 th day post-surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Cell apoptosis and autophagy are two important biological processes, which can be enhanced by oxidative stress [27]. H 2 O 2 has been widely utilized to construct oxidative stress injury model in many diseases [28,29]. In the present study, we also construct H 2 O 2 -induced cell injury model as the foundation for exploration of the effect of SNGH16 on the pathogenesis of SCI.…”
Section: R E T R a Cmentioning
confidence: 94%
“…The effect of H 2 O 2 is largely mediated by hydroxyl radicals (OH • ) generated by the Fenton reaction, which is catalyzed by Fe 2+ [ 55 ]. Previous studies have shown that Cu(II) also has an important role in the Fenton reaction to generate ROS [ 44 , 45 , 56 ].…”
Section: Resultsmentioning
confidence: 99%